Triazolization of Enolizable Ketones with Primary Amines: A General Strategy toward Multifunctional 1,2,3‐Triazoles - Prakash, Rashmi; Opsomer, Tomas; Dehaen, Wim (Chemical record, 2021)
The development of metal‐free syntheses toward 1,2,3‐triazoles has been a burgeoning research area throughout the past decade. Despite the numerous advances, the scarceness of methods for the preparation of 1,5‐disubstituted 1,2,3‐triazoles from readily available substrates remained a challenge that was addressed by our group in 2016. A metal‐free three‐component reaction, which we have dubbed the triazolization reaction, was established for the rapid synthesis of 1,5‐disubstituted, fully functionalized and NH‐1,2,3‐triazoles. This novel approach stands out because it utilizes widely available starting materials, namely primary amines and enolizable ketones. Furthermore, the broad substrate scope is a major advantage, and was further expanded by the number of modified protocols that have been reported. Triazolization products have successfully found utility as intermediates in various synthetic transformations, and were the subject of a few interesting biological activity studies. This account describes the first five years of developments since the discovery of the three‐component triazolization reaction. Starting from readily available enolizable ketones and primary amines or ammonium acetate, this method provides access to various 1,5‐di‐, (fused) 1,4,5‐trisubstituted and NH‐1,2,3‐triazoles. The triazolization reaction has already found utility in several synthetic pathways.